HIDROLISIS SELULOSA DARI POD HUSK KAKAO MENGGUNAKAN ASAM SULFAT - Lisin,Gatot S. Hutomo, dan Syahraeni Kadir, Nurwihadi (AGROTEKBIS, 2015)
The general objective of this study was to determine the effect of the concentration of NaOH in cellulose extraction of cocoa pod husk of the physical properties of cellulose, determine the relationship between was increased concentration of sulfuric acid (H2SO4) with glucose produced from cellulose hydrolysis process cocoa pod husk during hydrolysis and determine the rate of decay glucose levels after the achievement of the optimum point of hydrolysis of the cocoa pod husk. This study was consisted of two steps: (I) The extraction of cocoa pod husk using NaOH concentration of 10%, 12% and 14%, and (II) Hydrolysis of cellulose in various concentrations of H2SO4 ie: 1.0 M; 1.5 M; 2.0 M and 2.5 M. Variable observation in stage I includes yield and brightness were analyzed using a completely randomized design with advanced test Honestly Significant Difference (HSD) 1%. Furthermore, in the second stage is variable levels of glucose in various concentrations of H2SO4 and the glucose damages after the optimum point. The results showed that the concentration of NaOH 12% give the cellulose yield of 29.14% and 46.79% of brightness which is the best result for the production of cellulose as a raw material on step II in this research. Results of step II showed that the highest glucose levels found in H2SO4 concentration of 2.5%, amount to 23.17% at the optimum point of 6.70 hours with the correlation between the time of hydrolysis with the glucose production rate amounted to 77.22% where the damage occurred after the point optimum 7 hours. From the results of this study was concluded that the concentration of NaOH 12% is a better concentration in the extraction of cellulose from cocoa pod husk in particular on the yield and brightness of cellulose. There is a linear relationship between the concentration of sulfuric acid and glucose levels occur on the hour of 6 to 7 on process of hydrolysis of cellulose cocoa pod husk and the rate of the damage of glucose have been increased in line with increasing hydrolysis time after reaching the optimum point. The cocoa pod husk cellulose hydrolysis using H2SO4 should be not more than 7 hours due to the acid catalyst destructive glucose was produced. Necessary to study hydrolysis using other cellulosic feedstocks using an acid catalyst.